2009
DOI: 10.1002/chin.200945013
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Structure Analysis of Tetragonal Li7La3Zr2O12 with the Garnet‐Related Type Structure.

Abstract: Zirconium I 4400Synthesis and Structure Analysis of Tetragonal Li7La3Zr2O12 with the Garnet-Related Type Structure. -The title compound is synthesized by solid state reaction of Li2CO3, La2O3, and ZrO2 (alumina crucible, 1253 K, 5 h). Single crystals are obtained from 1:1 mixtures of the as-prepared material and Li2CO3 as a flux (gold crucible, 1313 K, 48 h). The compound has a garnet-related structure and crystallizes in the tetragonal space group I41/acd with Z = 8 (single crystal XRD). The structure contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 1 publication
5
53
1
Order By: Relevance
“…This is in line with previous observations, where the cubic phase is observed in undoped LLZO nanowires, but extended calcination causes particle growth and concomitant appearance of t-LLZO. 24 Reducing the size of LLZO to nanometric dimensions has been demonstrated 24 to produce undoped cubic LLZO (c-LLZO, space group Ia3̅ d), 3 whereas the thermodynamically favorable but poorly conducting tetragonal phase (t-LLZO, space group I4 1 /acd) 32 is formed in bulk LLZO in the absence of aliovalent dopants. This effect was also observed incidentally in several reports, 6,7,25,33 though not discussed in detail, and is hypothesized to originate from a sizestabilization effect of c-LLZO in undoped nanostructures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is in line with previous observations, where the cubic phase is observed in undoped LLZO nanowires, but extended calcination causes particle growth and concomitant appearance of t-LLZO. 24 Reducing the size of LLZO to nanometric dimensions has been demonstrated 24 to produce undoped cubic LLZO (c-LLZO, space group Ia3̅ d), 3 whereas the thermodynamically favorable but poorly conducting tetragonal phase (t-LLZO, space group I4 1 /acd) 32 is formed in bulk LLZO in the absence of aliovalent dopants. This effect was also observed incidentally in several reports, 6,7,25,33 though not discussed in detail, and is hypothesized to originate from a sizestabilization effect of c-LLZO in undoped nanostructures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This value is considerably lower than in other experiments where lower density materials were studied. 14,15,49 In the case of films with lower density, the contribution of the surface diffusion to the total conductivity will be more relevant. Assuming that the transport on the surface requires a higher activation energy, the effective activation energy of the films with a larger proportion of grain boundaries therefore will be higher.…”
Section: Li-ion Conductivitymentioning
confidence: 99%
“…2 Later, it was revealed that the garnet type structure of LLZO exists in two polymorphs: tetragonal structure (I4 1 /acd) stable at low temperature and cubic structure (Ia3̅ d) stable at high temperature; and the conductivity of the former is two order of magnitude lower than that of the latter. 3 Therefore, how to obtain garnet with the nominal composition of "Li 7 La 3 Zr 2 O 12 " and cubic structure has been attracting much attention. It has been suggested that supervalent cations can stabilize the cubic structure at room temperature by introducing Li vacancies and/ or decreasing the Li content.…”
Section: Introductionmentioning
confidence: 99%